2012
DOI: 10.1002/acr.20653
|View full text |Cite
|
Sign up to set email alerts
|

Association of body mass index with symptom severity and quality of life in patients with fibromyalgia

Abstract: Objective. To examine the association between body mass index (BMI) and symptom severity and quality of life (QOL) in patients with fibromyalgia. Methods. We assessed BMI status and its association with symptom severity and QOL in 888 patients with fibromyalgia who were seen in a fibromyalgia treatment program and who completed the Fibromyalgia Impact Questionnaire (FIQ) and the Short Form 36 (SF-36) health survey. Results. The BMI distribution of nonobese (BMI <25.0 kg/m 2 ), overweight (BMI 25.0 -29.9 kg/m 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
69
1
11

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(95 citation statements)
references
References 42 publications
14
69
1
11
Order By: Relevance
“…However, VAS and FIQ scores are positively correlated with BMI, BIA, and WC in patients with FMS. Previous research has demonstrated that, greater BMI is associated with greater pain severity, greater number of tender points, reduced physical strength and flexibility, and higher symptom burden in fibromyalgia [35][36][37].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, VAS and FIQ scores are positively correlated with BMI, BIA, and WC in patients with FMS. Previous research has demonstrated that, greater BMI is associated with greater pain severity, greater number of tender points, reduced physical strength and flexibility, and higher symptom burden in fibromyalgia [35][36][37].…”
Section: Resultsmentioning
confidence: 99%
“…In a study Kim et al [35] found that the groups with the greater BMI had greater fibromyalgia-related symptoms with worse FIQ total scores. These findings are similar to our results.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research has also examined the role of excess weight in patients diagnosed with fibromyalgia. For example, Kim and colleagues noted that individuals with a BMI greater than 35 reported greater symptom severity, as well as impairments in quality of life domains 43 . The current study suggests similar associations between fibromyalgia and lifestyle behaviors and provides fertile ground for future exploration of their impact on disease management and severity.…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, the occurrence of overweight and obesity is associated with the worsening of fibromyalgia symptoms (9,10). However, little is known about the role of adipokines in modulating fibromyalgia symptoms.…”
Section: Introductionmentioning
confidence: 99%